Virus Papiloma Humano - ELIZABETH BRAVO SALINAS, SARA; IRMA CARRIÓN ORDÓÑEZ, JULIA; AUGUSTA ESCANDÓN CARRIÓN, MARÍA; Escandón Carrión, Fabián Alejandro (Red Editorial Latinoamericana de Investigación Contemporánea, 2024)
Prologue****The Human Papillomavirus (hereinafter HPV) is a sexually transmitted infection that generally affects the oral and genital mucous membranes, causing growth (known as vegetations or warts) on the skin or mucous membranes, with more than 200 varieties. of the virus, causing benign pathologies in the majority of patients, however, some types are the cause of various cancers such as cancer of the anus, penis, vagina, vulva or oropharynx, with cervical cancer being the most frequent, the latter being It is one of the most silent cancers, being the fourth most common type of cancer in women worldwide, which is why it has become a global public health problem.**** ****Despite the multiple pathologies caused by HPV, there are currently vaccines to protect against strains that can cause genital warts or cervical cancer, although in most cases the immune system defeats the virus infection before to create warts. Many times, weeks or months, even years, have passed before they appear and the type of warts will be determined by the strain of the virus.**** ****In the case of cervical cancer, its development can take up to twenty years or more after an HPV infection, with the first stages being very silent, which can be evidenced with a Pap smear, which is why today it is It is essential to promote an adequate gynecological check-up, especially in sexually active women, in fertile periods and even postmenopausal women.****Although women over 65 can also have a Pap smear, they can stop having the test if they have had normal results on three Pap tests in a row or if they have had two human papillomavirus DNA tests and Pap tests without abnormal results.**** ****In any case, a timely check-up and test can allow for an adequate investigation, establishing appropriate treatment depending on the degree of affectation, which positively influences the future of the individual, their family and their environment. Therefore, this book describes the main characteristics of the virus and the main findings in the Ecuadorian population.**** ****Sara Elizabeth Bravo Salinas**** ****Doctor specializing in Family and Community Medicine****Master in Care of HIV Patients**** ****University Teaching Specialist****Catholic University of Cuenca